2012
DOI: 10.3109/00365521.2012.725089
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A in the tumor microenvironment of the human colorectal adenoma–carcinoma sequence

Abstract: IL-17A and TH17 are highly activated throughout the colorectal adenoma-carcinoma sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…IL-17A is continuously increased at the cancer stage, but is not associated with CRC patients' clinical pathological features. 31 In addition, we are also able to show that the stimulator factors (cytokines) for Th17 differentiation and expansion are also increased in the same patterns as IL-17A along the whole sequence, 31 indicating that increased IL-17A is probably from the activated Th17 cells. Thus, our findings suggest that the activation of Th17 cells may affect both the adenoma stage and cancer stage.…”
Section: Il-17a Promotes Formation Of Precancerous Adenoma and Initiamentioning
confidence: 86%
See 4 more Smart Citations
“…IL-17A is continuously increased at the cancer stage, but is not associated with CRC patients' clinical pathological features. 31 In addition, we are also able to show that the stimulator factors (cytokines) for Th17 differentiation and expansion are also increased in the same patterns as IL-17A along the whole sequence, 31 indicating that increased IL-17A is probably from the activated Th17 cells. Thus, our findings suggest that the activation of Th17 cells may affect both the adenoma stage and cancer stage.…”
Section: Il-17a Promotes Formation Of Precancerous Adenoma and Initiamentioning
confidence: 86%
“…29 Many changes including genetic, molecular, and histological alterations have been observed along the progression from human colorectal adenoma to CRC, 30 we have therefore examined that the expression level of IL-17A and Th17 cellstimulating factors (cytokines) both at the precancerous stage and cancerous stage. 31 We have found that the expression level of IL-17A is significantly elevated from the adenoma stage and throughout to the cancer stage. 31 At the adenoma stage, the expression level of IL-17A in the microenvironment is associated with the severity of dysplasia that has been recognized as one of the histological hallmark for cancer risk in patients with adenoma.…”
Section: Il-17a Promotes Formation Of Precancerous Adenoma and Initiamentioning
confidence: 97%
See 3 more Smart Citations